Nearby Hills ejecta as a probe of the gravitational potential of the Milky Way. Issue Volume 14:Issue S353(2019) (June 2019) - Zhang, Y. Q.; Smith, M. C.; McMillan, P. J.
Abstract: Stars ejected from the Galactic Center can be used to place important constraints on the Milky Way potential. We have used Hills stars to constrain models for the Galactic potential, demonstrating that meaningful constraint can be obtained if we have samples of around 50 nearby Hills stars.